Eve : templar one - Tony Gonzales (Tor Books, 2011)
"It is the year 23349 AD. The human race has no living memory of Earth, or its origins beyond a mysterious collapsed wormhole called the EVE Gate. Mankind has prospered in an age of posthumanism, but a powerful class of immortals are slowly taking control of the New Eden cluster. An epic war between the nation states, fought by fearless ship captains who can never die, is decimating the mortal populations of Read more...